Impact of isoniazid preventive therapy on the evaluation of long-term effectiveness of infant MVA85A vaccination - Bunyasi, E; Luabeya, A; Tameris, M; Geldenhuys, H; Mulenga, H; Landry, B; Scriba, T; Schmidt, B; Hanekom, W; Mahomed, H; McShane, H; Hatherill, M (International Union Against Tuberculosis and Lung Disease, 2017)
SETTING: South Africa. OBJECTIVE: To evaluate the long-term effectiveness of infant modified vaccinia Ankara virus-expressing antigen 85A (MVA85A) vaccination against tuberculosis (TB). DESIGN: We analysed data from a double-blind randomised placebo-controlled Phase 2b MVA85A infant TB vaccine trial (2009-2012), with extended post-trial follow-up (2012-2014). Isoniazid preventive therapy (IPT) was provided by public health services according to national guidelines. The primary outcome was curative treatment for TB disease. Survival analysis and Poisson regression were used for study analysis. RESULTS: Total follow-up was 10 351 person-years of observation (pyo). Median follow-up age was 4.8 years (interquartile range 4.4-5.2). There were 328 (12%) TB cases. TB disease incidence was 3.2/100 pyo (95%CI 2.8-3.5) overall, and respectively 3.3 (95%CI 2.9-3.9) and 3.0 (95%CI 2.6-3.5)/100 pyo in the MVA85A vaccine and placebo arms. A total of 304 children (11%) received IPT, with respectively 880 and 9471 pyo among IPT and non-IPT recipients. There were 23 (7.6%) TB cases among 304 IPT recipients vs. 305 (12.9%) among 2374 non-IPT recipients (P = 0.008). IPT effectiveness was 85% (95%CI 76-91). CONCLUSION: Extended follow-up confirms no long-term effectiveness of infant MVA85A vaccination, but a six-fold reduction in TB risk can be attributed to IPT. National TB programmes in high TB burden countries should ensure optimal implementation of IPT for eligible children.